Ensino por projetos como experiência educativa: um estudo sobre o projeto integrador do curso de arquitetura e urbanismo da FAEM/SC a partir de John Dewey - Fiore, Sedenir (2024)
This thesis, developed in the Fundamentals of Education research line of the Postgraduate Program in Education at UPF, analyzes the Integrative Project of the Architecture and Urbanism course at Faculdade Empresarial de Chapecó - FAEM/SC as an educational experience in a Deweyan sense. The research is justified by the need to understand to what extent the Teaching by Project approach contributes to training professionals in the Architecture and Urban Planning course from new perspectives. The research problem is formulated as follows: To what extent can the Integrative Project adopted in the Architecture and Urban Planning course at FAEM/SC be interpreted as an educational experience in the sense of John Dewey? The study adopts a qualitative approach, focusing on a case study. The methodology includes the analysis of curriculum documents, institutional records and reports on students' academic activities. In its structure, the research takes as its theoretical basis the notion of educational experience present in John Dewey's educational philosophy, the integration of project-based teaching in the learning theories most used in Architecture and Urbanism Courses, as well as the relationship between the Integrative Project and the objectives of the course, the changes made to the curricular matrix, the strengths and weaknesses identified in its pedagogical conception and indicates proposals for improvements for its continuity. The research results highlight the Integrator Project as a promising pedagogical approach for training architects and urban planners who are better prepared to face the challenges of contemporary society. The integration between theory and practice, combined with John Dewey's educational philosophy, offers an enriching perspective to promote the development of critical skills and students' commitment to social and environmental demands. However, some limitations of the Integrator Project were also identified, which point to the need for its continuous improvement, seeking to integrate new methodologies and educational references capable of promoting greater interdisciplinarity and encouraging student engagement in actions with a positive social and environmental impact.